Analysis of Mattress Product Quality Using Seven Tools Method; a Case Study: UD. Pandawa Lima - Bagus Wahyu Prayoga; Deny Andesta (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
UD. Pandawa Lima is a micro-business that produces mattresses. Product defects occur at UD. Pandawa Lima are stitching defects, mattress foam defects, and faded color defects. The purpose of this study is to use the seven tools method to find the most dominant defects and propose improvements to defects. The results showed that the most dominant defects occurred in faded color defects of 50 pcs with a percentage of 48.08%. Proposed improvements that need to be implemented are to add adequate rest hours to reduce excessive stitching defects, scheduling machine maintenance to reduce seam defects and foam size defects, choosing a reliable and good supplier to reduce faded color defects and foam size defects, and improve the production process methods to reduce color fading defects, stitch defects, foam size defects. The product defects occurred are still under controlled, it does not exceed the upper and lower control limits. There is a positive correlation, the higher production the higher level of defect in the product. UD. Pandawa Lima merupakan usaha mikro yang memproduksi kasur. Kecacatan produk yang dialami oleh UD. Pandawa Lima yaitu cacat jahitan, cacat busa kasur, dan cacat warna pudar. Tujuan penelitian ini adalah menggunakan metode seven tools untuk mencari kecacatan yang paling dominan dan mengungkap usulan perbaikan terhadap kecacatan yang ada. Hasil penelitian menunjukkan tingkat kecacatan paling dominan terjadi pada cacat warna pudar sebanyak 50 pcs dengan presentase 48.08%. Usulan perbaikan yang perlu diterapkan yaitu menambahkan jam istirahat yang cukup untuk memperbaiki cacat jahitan berlebih; penjadwalan perawatan mesin untuk mengurangi cacat jahitan dan cacat ukuran busa; memilih supplier yang terbaik untuk mengurangi cacat warna pudar dan cacat ukuran busa; dan perbaikan metode proses produksi untuk mengurangi cacat warna pudar, cacat jahitan, cacat ukuran busa. Kecacatan produk yang dialami masih terkendali dengan baik karena tidak melewati batas kendali atas maupun batas kendali bawah. Terdapat korelasi positif pada penelitian, apabila jumlah produksi tinggi maka tingkat kecacatan pada produk semakin tinggi.